Individual differences in a spatial-semantic virtual environment - Chen, Chaomei (Journal of the American Society for Information Science, 2000)
This article presents two studies concerning the role of individual differences in searching through a spatial‐semantic virtual environment. In the first study, 10 subjects searched for two topics through a spatial user interface of a semantic space. A strong positive correlation was found between associative memory (MA‐1) and search performance (r = 0.855, p = 0.003), but no significant correlation was found between visual memory (MV‐1) and search performance. In the second study, 12 subjects participated in a within‐subject experimental design. The same spatial user interface and a simple textual user interface were used. The effects of spatial ability (VZ‐2), associative memory (MA‐1), and on‐line experience were tested on a set of interrelated search performance scores. A statistically significant main effect of on‐line experience was found, F(6, 4) = 6.213, p = 0.049, two‐tailed. In particular, on‐line experience has a significant effect on the recall scores with the textual interface. Individuals experienced in on‐line search are more likely to have a higher recall score with the textual interface than less experienced individuals. No significant main effects were found for spatial ability and associative memory. Subjects' comments suggest a potentially complex interplay between individuals' mental models and the high‐dimensional semantic model. Qualitative and process‐oriented studies are, therefore, called for to reveal the complex interaction between individuals' cognitive abilities, domain knowledge, and direct manipulation skills. A recommendation is made that spatial‐semantic models should be adaptable to suit individuals and tasks at various levels.